Strategi Perempuan dalam Memimpin Kelompok Kerja Bina Sehat (KKBS) Wilayah Jember - Rio Putra Pratama; Belgis Hayyinatun Nufus; Ria Faisyahril (TUTURAN: Jurnal Ilmu Komunikasi, Sosial dan Humaniora, 2025)
The Bina Sehat Working Group (KKBS) is a health-based social welfare institution that focuses on handling Human Immunodeficiency Virus/ Acquired Immune Deficiency Syndrome or HIV/AIDS among gays, transgender people, injecting drug users and commercial sex workers. KKBS has three regions which include, namely Banyuwangi, Jember, and Situbondo, each region consisting of people who have similar backgrounds to the client. If the targeted client is gay, then the KKBS members of that region are also gay. However, the Jember Region KKBS is unique in that its leadership is held by women, who have different gender and sexual identities from its members who are gay. However, the achievement target of the Jember Region KKBS is the highest achievement target compared to the other two regions. This paper discusses the strategies used by women in leading the Jember Region KKBS. This research uses the leadership strategy theory put forward by Prasinta, Jarkawi, and Kase in analyzing research findings. The results of this research are that women in leading the Jember Region KKBS use a combination of various leadership strategies, namely participative leadership strategies, transformational leadership strategies, situational leadership strategies, collaborative leadership strategies, and servant leadership strategies.